Bacterial lipases: A review on purification and characterization - Javed, Saira; Azeem, Farrukh; Hussain, Sabir; Rasul, Ijaz; Siddique, Muhammad Hussnain; Riaz, Muhammad; Afzal, Muhammad; Kouser, Ambreen; Nadeem, Habibullah (Progress in biophysics and molecular biology, 2018)
Lipase (E.C.3.1.1.3) belongs to the hydrolases and is also known as fat splitting, glycerol ester hydrolase or triacylglycerol acylhydrolase. Lipase catalyzes the hydrolysis of triglycerides converting them to glycerol and fatty acids in an oil-water interface. These are widely used in food, dairy, flavor, pharmaceuticals, biofuels, leather, cosmetics, detergent, and chemical industries. Lipases are of plant, animal, and microbial origin, but microbial lipases are produced at industrial level and represent the most widely used class of enzymes in biotechnological applications and organic chemistry. Phylogenetic analysis and comparison of residues around GxSxG motif provided an insight to the diversity among bacterial lipases. A variety of para-Nitrophenyl (p-NP) esters having C2 to C16 (p-NP acetate to p-NP palmitate) in their fatty acid side chain can be hydrolyzed by bacterial lipases. Large heterogeneity has been observed in molecular and catalytic characteristics of lipases including molecular mass; 19–96 kDa, Km; 0.0064–16.58 mM, Kcat; 0.1665–1.0 × 104 s−1 and Kcat/Km; 26.02–7377 s-1/mM. Optimal conditions of their working temperature and pH have been stated 15–70 °C and 5.0–10.8, respectively and are strongly associated with the type and growth conditions of bacteria. Surface hydrophobicity, enzyme activity, stability in organic solvents and at high temperature, proteolytic resistance and substrate tolerance are the properties of bacterial lipases that have been improved by engineering. Bacterial lipases have been extensively studied during last decade. However, their wider applications demand a detailed review on purification, catalytic characterization and applications of lipases.